2017
DOI: 10.1016/j.jid.2017.06.019
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Antibiotic Exposure Causes Intestinal Dysbiosis and Exacerbates Skin and Lung Pathology in Experimental Systemic Sclerosis

Abstract: Patients with systemic sclerosis (SSc) display altered intestinal microbiota. However, the influence of intestinal dysbiosis on the development of experimental SSc remains unknown. Topoisomerase I peptide-loaded dendritic cell immunization induces SSc-like disease, with progressive skin and lung fibrosis. Breeders were given streptomycin and pups continued to receive antibiotic (ATB) until endpoint (lifelongATB). Alternately, ATB was withdrawn (earlyATB) or initiated (adultATB) during adulthood. Topoisomerase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…15,43 Similarly, treatment of mice with antibiotics until weaning led to increased susceptibility to skin and lung fibrosis in a model of systemic sclerosis. 18 Furthermore, using the house dust mite (HDM) model of lung allergy, Marsland's team showed that exposure of mice to microbiota during the second week after birth imprinted efficient generation of Tregs later in life, which modulated HDM-induced inflammation. 16 A similar observation by Rosenblum's team was reported for the generation of skin-resident Tregs that regulate microbiota-induced inflammation in adulthood.…”
Section: A Fetal Time Window?mentioning
confidence: 99%
See 1 more Smart Citation
“…15,43 Similarly, treatment of mice with antibiotics until weaning led to increased susceptibility to skin and lung fibrosis in a model of systemic sclerosis. 18 Furthermore, using the house dust mite (HDM) model of lung allergy, Marsland's team showed that exposure of mice to microbiota during the second week after birth imprinted efficient generation of Tregs later in life, which modulated HDM-induced inflammation. 16 A similar observation by Rosenblum's team was reported for the generation of skin-resident Tregs that regulate microbiota-induced inflammation in adulthood.…”
Section: A Fetal Time Window?mentioning
confidence: 99%
“…[11][12][13][14][15] While earlier studies have focused on the intestine, similar observations were reported for the lung and skin, thus generalizing the "window of opportunity" concept to other mucosal surfaces. [16][17][18][19] A similar "window of opportunity" may exist during late fetal life, 10,20,21 even though its consequences, mechanisms and time limits remain to be more precisely defined.…”
Section: Introduction: Microbes Hygiene and Imprinting Of The Immunementioning
confidence: 99%
“…Epigenetic factors are potential contributors to SSc fibrogenesis; for example, particular microRNAs, including miR-155, are associated with lung fibrosis [45] and bromodomain inhibitors having potential anti-fibrotic effects in SSc lung fibroblasts [46]. Additional complex gene-environment interactions likely contribute to lung pathology in SSc; for example, experimental studies support a role for the microbiome, with early antibiotic exposure associated with increased susceptibility to experimental lung fibrosis in a scleroderma mouse model [47].…”
Section: [H2] Pathogenesis Of Lung Fibrosismentioning
confidence: 99%
“…To maximize the value of preclinical SSc models, whether for understanding pathogenesis or evaluating the efficacy and mode of action of novel therapies, a combination strategy using multiple complementary disease models is recommended (Del Galdo and Matucci-Cerinic, 2014). Mehta et al (2017) present an interesting and potentially informative novel approach to model SSc predicated on the putative roles of dendritic cells and topoisomerase-I-specific autoimmunity. The authors performed immunization with dendritic cells loaded with the topoisomerase-I peptide to induce immunity, inflammation, and skin and lung fibrosis in BALB/c mice.…”
Section: Preclinical Disease Models For Ssc: An Innovative Cellular Imentioning
confidence: 99%
“…Early-life gut dysbiosis influences fibrosis propensity in the mouse Employing their innovative immunization-induced disease model, Mehta et al (2017) advance a relatively novel concept for SSc pathogenesis based on gut dysbiosis. The gut microbiome represents a dynamic ecosystem that is relatively stable in adults, but is shaped by early-life exposures.…”
Section: Preclinical Disease Models For Ssc: An Innovative Cellular Imentioning
confidence: 99%